Aplicación de un sistema de costos por órdenes de producción en la productora y comercializadora de helados de Salcedo Corpicecream s.a del cantón Salcedo, provincia de Cotopaxi, durante el período 01 de enero al 30 de junio del 2013 - Gallo Silva, Sonia Paola (2015)
This research carried out in the Company CORPICECREAM S. A, has as a objective obtain the unit value and profit of production that generates each elaborated products developed through the application of a Cost System by orders of production, it is a tool for proper control of cost elements allowing accurately identify the benefit in each of the products. During the analysis were applied the methods of research that helped us to collect information through the interview, the respective methodological guide that is used in the Cost System by orders of production were applied, helped identify the F.O.D.A analysis in order to obtain a sample leading to the researchers to have a general understanding of the company. Inside the Cost System by orders of production a process that begins with source, transactions, journal, majorization, trial balance and financial statements. Today is very important for companies that produce through orders opting for a System, which allows them to identify the production elements and Know the real cost unit of the finish product, permitting evaluate if the profit is appropriate for that the manager and directors, to acquire an adequate decision-making.